The implications and management of complex biliary injuries at a tertiary hepatobiliary specialty center - Rasha T Kakati; Mohamad Othman; Hussein Kharroubi; Karim Ataya; Hussein Nassar; Bassel Hafez; Walid Faraj; Mohamad Jawad Khalife (SAGE Open Medical Case Reports, 2022)
Injuries of the biliary tract and complex injuries involving vascular and parenchymal tissue can be detrimental despite the improved use of laparoscopy. Complex biliary injuries are variable depending on the type of injury as well as patient and surgeon factors. We present four cases of complex biliary injuries at our tertiary referral center with hepatobiliary expertise: biliary stenosis with obstruction, double duct system anatomy, combined right hepatic arterial transection and biliary duct injury, and a complete pedicle injury. Early identification and specialized repair of complex biliary injuries is essential to minimize patient morbidity. Notably, consulting a specialist intraoperatively in case of difficult dissection and visualization or a suspected injury and considering bail-out strategies such as a subtotal cholecystectomy or conversion are safe approaches to minimize complex biliary injuries. Earlier recognition and repair of complex biliary injuries improves outcomes when immediate intraoperative repair can be performed rather than delayed postoperatively.